Association between serum and urine biomarkers and lumbar spine individual radiographic features: The Johnston County Osteoarthritis Project - Goode, Adam P. (2012)
OBJECTIVE: 1) To determine associations between radiographic features of lumbosacral spine disc space narrowing (DSN) and osteophytes (OST) and joint metabolism biomarkers (serum cartilage oligomeric matrix protein (COMP), hyaluronic Acid (HA), collagen neoepitope (C2C), C-propeptide of type II procollagen (CP-II), urine C-terminal cross-linking telopeptide (CTX-II) and N-terminal telopeptide (NTX-I)). 2) To explore interactions with race, gender and low back symptoms. DESIGN: Cross-sectional analysis of 547 participants enrolled in the Johnston County Osteoarthritis Project from 2003–2004. Mean biomarker levels were estimated with linear regression. Proportional and partial proportional odds models were used to estimate associations. Interactions were tested with likelihood ratio tests at a p-value<0.10. Biomarkers were natural log (ln) transformed. RESULTS: Significant differences in mean biomarker levels were found across severity of DSN for lnHA and lnC2C and lnCTX-II across severity of both DSN and OST. Moderate to strong associations were found between biomarkers of type II collagen and DSN, whereas associations with OST were weak. An association between lnHA and DSN was seen in women (adjusted odds ratio [aOR]=1.34 (95% CI 1.08, 1.65)) but no association among men (aOR=0.90 (95% CI 0.63, 1.26)). In Caucasians there was a decreased association with NTX-I and OST (aOR=0.67 (95% CI 0.49, 0.91)) and no association in African Americans (aOR=1.06 (95% CI 0.76, 1.47)). There was a positive association of lnCOMP with DSN among those with low back symptoms (aOR=1.82 (95% CI 1.02, 3.27)), but no association in those without low back symptoms (aOR=0.65 (95% CI 0.35, 1.20)). CONCLUSION: Joint metabolism biomarkers suggest biological differences in the pathologic process involved in DSN and OST that may be gender (HA) and ethnicity (NTX-I) specific.